Correction: An updated roadmap for the integration of metal–organic frameworks with electronic devices and chemical sensors. (6th June 2017) - Stassen, Ivo; Burtch, Nicholas C.; Talin, A. Alec; Falcaro, Paolo; Allendorf, Mark D.; Ameloot, Rob
Abstract : Correction for 'An updated roadmap for the integration of metal–organic frameworks with electronic devices and chemical sensors' by Ivo Stassen et al., Chem. Soc. Rev., 2017, DOI: 10.1039/c7cs00122c.